Teachers' Perception toward e-LKPD STEM-EDP to Improve System Thinking Skills and Creative Problem Solving Skills - Alyana Atina; Kartini Herlina; Abdurrahman (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the needs of teachers and students in physics education, focusing on renewable energy. It aims to describe a valid e-LKPD (electronic student worksheet) for Alternative Energy Learning based on the STEM Engineering Design Process (EDP) to enhance students' System Thinking Skills and Creative Problem Solving Skills through qualitative and quantitative methods. A survey of 20 high school physics teachers in Lampung Province revealed that 77.8% use the STEM model for teaching, but only 72.2% of students engage in setting goals and defining problems. These findings indicate that current e-LKPDs are inadequate, lacking activities to develop the necessary skills. Thus, there is a clear need for more effective e-LKPDs to provide a more engaging and comprehensive learning experience.